LEGAL REVIEW ON MARRIAGE CANCELLATION POST SERMON (Case Study in Mattampa, Pangkep Regency) - Zulkifli Zulkifli; Firman Firman; Andi Mahfud Fudail; Nasrul Nasrul; Ilham Latif (Jurnal Ilmiah Global Education, 2023)
This study aims to find out how and how much the community responds to a case of Post-Khitbah Marriage Cancellation in Mattampa, Pangkep Regency. Which is described in the sub-problem: What is the concept of khitbah and the social consequences of canceling a marriage after khitbah on the community in Mattampa, Pangkep Regency. How is the legal review regarding the cancellation of marriage after the khitbah in Mattampa, Pangkep Regency. Answering the problems raised, then pursued through a juridical analysis approach, while the type of research conducted is qualitative research.